1996
DOI: 10.1103/physrevlett.76.1627
|View full text |Cite
|
Sign up to set email alerts
|

Bragg Grating Solitons

Abstract: We report the first experimental observation of nonlinear propagation effects in fiber Bragg gratings, resulting in nonlinear optical pulse compression and soliton propagation. The solitons occur at frequencies near the photonic band gap of the grating; they are due to a combination of the negative dispersion of the grating, which dominates the material dispersion, and self-phase modulation. The solitons propagate at velocities well below the speed of light in the uniform medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
373
1
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 634 publications
(385 citation statements)
references
References 8 publications
(8 reference statements)
8
373
1
3
Order By: Relevance
“…(2.1a) and (2.1b) take the simplest form in the case v = 0, corresponding to a pulse of standing light. In reality, the soliton observed by Eggleton, Slusher, de Sterke, Krug and Sipe [1996] was moving at a considerable velocity. Generation and detection of zero-velocity solitons in nonlinear Bragg gratings remains an experimental challenge.…”
Section: Introduction § § § Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…(2.1a) and (2.1b) take the simplest form in the case v = 0, corresponding to a pulse of standing light. In reality, the soliton observed by Eggleton, Slusher, de Sterke, Krug and Sipe [1996] was moving at a considerable velocity. Generation and detection of zero-velocity solitons in nonlinear Bragg gratings remains an experimental challenge.…”
Section: Introduction § § § Introductionmentioning
confidence: 99%
“…Figure 1: Experimental evidence for the existence of solitons in a nonlinear optical fiber with Bragg grating: the broad pulse is far from a Bragg resonance and has passed the fiber without interacting with the grating; the narrow one is a soliton shaped by Bragg-resonant interaction with the grating (see further details in the work by Eggleton, Slusher, de Sterke, Krug and Sipe [1996]). …”
Section: Introduction § § § Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that approximately half of the gap-soliton family is stable, and the other half unstable (the solitons with positive and negative intrinsic frequencies are, respectively, stable and unstable). Moving BG solitons (with the velocity no less than half the group ve-locity of light in the same material) have been created experimentally in silica fibers with the BG written in the cladding [9,10].…”
Section: Introduction and The Modelsmentioning
confidence: 99%